Exploring the mediating role of mathematics self-efficacy in students’ perceptions and achievement in mathematics - John V. de Vera; Jehan Marie T. Aytona; Beverly U. Mamogay; Rogard A. Bardinas; Shella Mary N. Canaricio; Emerson D. Peteros (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study examined the mediating effect of mathematics self-efficacy (MSE) on the relationship between students’ perception of mathematics (SPM) and mathematics achievement (MA) among 544 Grade 9 students from selected public high schools in Mandaue City, Philippines, using a descriptive correlational research design. Participants were selected through simple random sampling. Data were collected using adopted survey questionnaires to measure SPM and MSE, while MA was obtained from first-quarter grades. The data collected were treated using frequency count, percentage, weighted mean (WM), standard deviation (SD), Pearson’s r, and multiple regression. Results indicated that students demonstrated neutral SPM, moderate MSE, and satisfactory MA. Moreover, there was a significant moderate positive relationship between SPM and MSE (r=0.627, p<0.001), while negligible positive correlations were observed between SPM and MA (r=0.216, p<0.001) and between MSE and MA (r=0.205, p<0.001). Furthermore, results also revealed that MSE partially mediated the relationship between SPM and MA, accounting for 33.4% of the total effect (indirect effect β=0.597, p=0.037). These findings suggest that teachers and school administrators should integrate self-efficacy building strategies including supportive feedback, engaging, and inclusive learning environments that enhance students’ perception and achievement in mathematics.